PERAN OJK DALAM PENCEGAHAN FRAUD PADA EQUITY CROWDFUNDING: STUDI PERBANDINGAN DENGAN MEKANISME PENGAWASAN PERBANKAN - Rizki, Amanda Amelia; Savitri, Ina Kurnia; Bakhtiar, Irsya (UI Scholars Hub, 2026)
This study examines the role of the Financial Services Authority (Otoritas Jasa Keuangan/OJK) in preventing fraud in the implementation of Equity Crowdfunding (ECF) in Indonesia and compares it with the supervisory mechanisms of the banking sector, which are based on the prudential principle. Using a normative juridical approach and a comparative regulatory study, the research finds that although Financial Services Authority Regulation No. 17 of 2025 concerning the Offering of Securities through Information Technology Based Crowdfunding Services (POJK No. 17 of 2025) has strengthened the regulatory framework for ECF through licensing requirements, off-site and on-site supervision, issuer due diligence obligations, and the application of basic governance principles, these mechanisms have not yet reached the depth of supervision applied in the banking sector. Banking supervision applies the prudential principle comprehensively through risk management, capital adequacy, internal controls, and layered supervisory mechanisms, thereby enabling more effective mitigation of fraud risks. In contrast, supervision of ECF remains largely administrative in nature, reporting-based, and tends to be reactive to fraud cases as they arise. The findings indicate that several prudential banking principles are in fact relevant to be adopted within the ECF supervisory framework; however, their implementation remains limited. Therefore, the effectiveness of OJK’s supervision over ECF is considered suboptimal and requires the strengthening of risk-based supervisory mechanisms as well as enhanced supervisory technology capacity in order to keep pace with the dynamics of fintech innovation